Optic disc drusen and scleral canal size – protocol for a systematic review and meta-analysis - Vienne-Jumeau, Aliénor; Brémond-Gignac, Dominique; Robert, Matthieu P. (Frontiers in Ophthalmology, 2023)
Background: Around one in fourty patients are diagnosed with optic disc drusen (ODD) during their lifetime. Complications of these acellular deposits range from asymptomatic visual field deficits to artery occlusion and subsequent cecity. Still, the pathogenesis of their emergence remains controversial. In particular, it was suggested 50 years ago that a narrow disc and scleral canal is one factor leading to axoplasmic flow disturbance, which induces ODD formation. However, this hypothesis is still debated today. To evaluate the basis of this theory, we will conduct a systematic review and meta-analysis of studies evaluating the scleral canal size in patients with ODD and in healthy subjects.Methods: We will search MEDLINE via PubMed, Cochrane, and EMBASE electronic databases to identify articles published before November 29, 2022 that measure the scleral canal size in patients with ODD and in healthy subjects. In addition, grey literature will be searched. The meta-analysis will include studies that include patients with a clinical or imaging diagnosis of ODD and healthy subjects. Additionally, we will perform a subgroup analysis to compare patients with buried ODD and patients with visible ODD. Extracted data from included studies will be presented descriptively, and effect sizes will be computed based on the recommendations from the Cochrane Collaboration handbook.Discussion: The hypothesis that a narrow scleral canal is a risk factor of ODD has long been debated and this systematic review and meta-analysis should disentangle the different views. Understanding the underlying factors driving the development of ODD should help us focus on patients at risk and develop strategies to prevent advanced stages of the disease in these patients. Besides, focusing on patients with small scleral canals should help us derive associated factors and provide a better understanding of the pathology.